Fluorescence in Industry - Pedras, Bruno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers 12 outstanding contributions that reflect state-of-the-art industrial applications of fluorescence, ranging from the pharmaceutical and cosmetics industries to explosives detection, aeronautics, instrumentation development, lighting, photovoltaics, water treatment and much more. In the field of fluorescence, the translation of research into important applications has expanded significantly over the past few decades. The 18th volume in the Springer Series on Fluorescence fills an important gap by focusing on selected industrial applications of fluorescence, described in contributions by both industry-based researchers and academics engaged in collaborations with industrial partners. .
Luminescence-Based Sensors for Bioprocess Applications -- Fluorescence in Pharmaceutics and Cosmetics -- Instrumentation for Fluorescence Lifetime Measurement using Photon Counting -- Applications of Submersible Fluorescence Sensors for Monitoring Hydrocarbons in Treated and Untreated Waters -- Luminescence in Photovoltaics -- Time-Gated Luminescence Acquisition for Biochemical Sensing: miRNA Detection -- Thermally Activated Delayed Fluorescence Emitters for Light Emitting Diodes and Sensing Applications -- Explosives Detection: From Sensing to Response -- New Trends in Fluorescent Reporters in Biology -- Application of Fluorescence in Life Sciences for Basic Research and Medical Diagnostics -- Photoluminescent Glasses and their Applications -- Luminescence-Based Sensors for Aeronautical Applications.
Keywords: Spectrum analysis; Pharmaceutical chemistry; Biochemistry; Chemistry, Technical; Physical chemistry; Medicinal chemistry; Spectroscopy; Pharmaceutics; Biochemistry; Industrial Chemistry; Physical Chemistry; Medicinal Chemistry